SISTEM INFORMASI PENDAFTARAN ONLINE SMP IT AR-RIDLO BERBASIS WEB DENGAN PHP DAN SQL - Mochammad Sabillah, Pasha; Wahyuni, Tantri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
SMP IT AR-RIDLO Jatiwangi is an integrated Islamic junior high school that originated from the AR-RIDLO Peduli Pendidikan Foundation. Construction began in 2010, and the school started operations in 2011 to accommodate students who wish to learn but whose parents are financially unable. The issues faced include problems with the registration data processing for prospective students, which is not yet computerized, and the absence of proof of registration for prospective students. Other issues include the lack of computerized creation of applicant summaries and summaries of accepted or rejected applicants. Therefore, a comprehensive information system is needed to assist with the management of the school website’s dashboard, and the generation of reports for applicant summaries and the statuses of accepted or rejected applicants. This system should integrate previously non-computerized components into a single system, enabling a more effective and faster process using the Waterfall method.